Framing Classical Reception Studies : Different Perspectives on a Developing Field - Haan, Nathalie De,; Pourcq, Maarten De,; Rijser, David, (Metaforms ;, 2020)
Framing Classical Reception Studies contains a representative number of analytic and synthetic contributions by scholars from diverse parts of the field of Classical Reception Studies. Together, they afford a synoptic view and typology of an extremely large and continuously diversifying discipline. Attentive to questions such as what, by whom, in what contexts and to what ends Classics have functioned and are functioning in our culture, all contributors ask themselves from what conceptual or disciplinary frame they approach the reception of the cultures of classical Greek and Roman antiquity. Within this questioning format, the book also contains suggestions for future agendas of research, and forcefully argues for the political, cultural and cognitive relevance of classical receptions in the Academy.